Wage-price standards and economic policy - Meyer, Jack A. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1982)
This study assesses the wage-price policy pursued by the U S Council on wage and price stability during the six years existence from 1974 to 1980.
aia 20/03/2019
Loans
Keywords: Wage-price policy; United States